Functional analysis of bispecific antibody (EpCAMxCD3)-mediated T-lymphocyte and cancer cell interaction by single-cell force spectroscopy - Hoffmann, Sabrina; Wabnitz, Guido H.; Samstag, Yvonne; Moldenhauer, Gerhard; Ludwig, Thomas (International journal of cancer, 2011)
The atomic force microscopy (AFM) is a powerful tool to analyze forces generated on cellular interactions on the single-cell level. This highly sensitive device can record changes in force in the pico-Newton range, which equals single molecule bonds. Here, we have used single-cell force spectroscopy by AFM to investigate the interaction between T cells and tumor cells that is induced by the bispecific antibody HEA125xOKT3 (specificity anti-EpCAMxCD3). We show that HEA125xOKT3 induces a specific increase in adhesion force between T cells and cancer cells. The adhesive force that is generated on cell-cell contact is dependent on the applied force on initial contact and the duration of this initial contact. In summary, HEA125xOKT3 has been found to mediate contact formation by distinct processes. It induces direct cell-cell interaction, which results in the activation of T-cell signaling, facilitates the formation of supramolecular activation clusters and ultimately of an immune synapse.
First published: 08 March 2011
Gesehen am 11.07.2022